2016
DOI: 10.1590/bjpt-rbf.2014.0173
|View full text |Cite
|
Sign up to set email alerts
|

Dynamometry for the measurement of grip, pinch, and trunk muscles strength in subjects with subacute stroke: reliability and different number of trials

Abstract: BackgroundMuscle strength is usually measured in individuals with stroke with Portable dynamometers (gold standard). However, no studies have investigated the reliability, the standard error of measurement (SEM) and the minimal detectable difference (MDD95%) of the dynamometry for the measurement of hand grip, pinch grip and trunk strength in subjects with subacute stroke.Objective1) To investigate the intra and inter-rater reliability, the SEM and the MDD95% of the portable dynamometers for the measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
0
31
0
3
Order By: Relevance
“…Previous studies that investigated whether dynamometry strength measures based upon various numbers of trials were statistically different, found similar results for the following muscle groups: grip; pulp‐to‐pulp, palmar, and lateral pinch; and trunk flexors/extensors, lateral flexors, and rotators of individuals with sub‐acute (.92 ≤ P ≤ .99) and chronic (.85 ≤ P ≤ .99) stroke. In addition, Coldham et al reported that only a single trial of grip strength, measured with a dynamometer, in healthy individuals and in individuals who had undergone orthopedic surgery, is as reliable as the mean and the best value of 3 trials .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Previous studies that investigated whether dynamometry strength measures based upon various numbers of trials were statistically different, found similar results for the following muscle groups: grip; pulp‐to‐pulp, palmar, and lateral pinch; and trunk flexors/extensors, lateral flexors, and rotators of individuals with sub‐acute (.92 ≤ P ≤ .99) and chronic (.85 ≤ P ≤ .99) stroke. In addition, Coldham et al reported that only a single trial of grip strength, measured with a dynamometer, in healthy individuals and in individuals who had undergone orthopedic surgery, is as reliable as the mean and the best value of 3 trials .…”
Section: Discussionmentioning
confidence: 75%
“…Consequently, there is less chance for the regression toward the mean phenomenon to occur . Because hand‐held dynamometers have shown to provide reliable measures of strength of the upper and lower limb muscles of individuals with stroke (0.58 ≤ correlation coefficient ≤ 0.99) , this may justify the findings; that is, similar values were provided by different scoring methods.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Considering that the association between grip strength and lower-limb muscle function has been proved to be a relevant parameter to be investigated in older adult population [17], investigating this association in different populations with muscle weakness and disabilities becomes necessary. In this context, post-stroke individuals must be considered, since this population commonly present lower thresholds for muscle fatigue as well as muscle weakness [12,19]. Thus, a fast and objective measure such as grip strength would optimize the clinical evaluation process by informing about lower-limb global strength.…”
mentioning
confidence: 99%